2012
DOI: 10.1111/j.1463-1326.2012.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment persistence, hypoglycaemia and clinical outcomes in type 2 diabetes patients with dipeptidyl peptidase‐4 inhibitors and sulphonylureas: a primary care database analysis

Abstract: Lack of persistence with antidiabetic therapy is frequently found in primary care patients. DPP-4 was associated with lower therapy discontinuation and a fivefold reduced frequency of patients with hypoglycaemia compared to SU. The low absolute numbers of hypoglycaemias are most likely due to the fact that only severe events were documented. DPP-4 treatment was associated with reduced incidence of macrovascular events relative to SU in type 2 diabetes patients in primary care practises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
1
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 26 publications
8
76
1
9
Order By: Relevance
“…We used the German Disease Analyzer database (IMS Health), which includes patient data entered by general practices throughout Germany (15)(16)(17). Practices are anonymously reporting all diagnoses (ICD-10), prescriptions (Anatomical Therapeutic Chemical [ATC] Classification System), hospital admissions, and laboratory test results on an ongoing basis.…”
Section: Study Population Assessment Of Variablesmentioning
confidence: 99%
“…We used the German Disease Analyzer database (IMS Health), which includes patient data entered by general practices throughout Germany (15)(16)(17). Practices are anonymously reporting all diagnoses (ICD-10), prescriptions (Anatomical Therapeutic Chemical [ATC] Classification System), hospital admissions, and laboratory test results on an ongoing basis.…”
Section: Study Population Assessment Of Variablesmentioning
confidence: 99%
“…We screened 1273 citations and included 17 studies with a total of 1498358 participants in the meta-analysis (Bonds et al, 2010, Chiba et al, 2015, Duckworth et al, 2011, Hsu et al, 2013, Origin Trial Investigators et al, 2013, Johnston et al, 2012, Johnston et al, 2011, Khunti et al, 2015, Majumdar et al, 2013, McCoy et al, 2012, Rajpathak et al, 2015, Rathmann et al, 2013, Signorovitch et al, 2013, Zhao et al, 2012, Zoungas et al, 2010. The flow chart of the study selection in shown in the supplementary eFigure.…”
Section: Resultsmentioning
confidence: 99%
“…Association between hypoglycaemia and vascular disease (Figure 1) We included eight studies in the meta-analysis for macrovascular complications (Duckworth et al, 2011, Hsu et al, 2013 , Johnston et al, 2011, Khunti et al, 2015, Rathmann et al, 2013, Zhao et al, 2012, Zoungas et al, 2010 There are two studies in the meta-analysis which reported on the association between hypoglycaemia and microvascular complications (Zhao et al, 2012, Zoungas et al, 2010. The pooled odds ratio was 1.77 (95% Confidence Interval 1.49, 2.10) with no evidence of heterogeneity (chi-squared p= 0.90, I 2 =0%).…”
Section: Meta-analysismentioning
confidence: 99%
“…La falta de cambio significativo de peso desde la basal, también confirma lo descrito en la literatura con iDPP4 14 , que aparecen como hipoglicemiantes con efecto neutro sobre el peso, a diferencia de lo que ocurre con SU e insulina que producen aumento de peso en el tiempo [9][10][11][12][13][14] . En una enfermedad de prevalencia creciente como lo es la DMT2 en nuestro país y en el mundo 15 , de carácter progresivo y crónico, se requiere de una terapia efectiva, con la menor cantidad de eventos adversos posibles para lograr mejor adherencia y control a largo plazo, de manera de minimizar las complicaciones micro y macrovasculares 16,17 . Vildagliptina muestra en este estudio de vida real un perfil de eficacia y seguridad adecuado y consistente, probablemente mejorando la funcionalidad de las células pancreáticas [18][19] y con cambios en metabolismo glicémico, convirtiéndose así en una alternativa terapéutica oral para los DMT2 chilenos.…”
Section: Discussionunclassified